2000
DOI: 10.1016/s0743-1066(00)00006-6
|View full text |Cite
|
Sign up to set email alerts
|

A simple polynomial groundness analysis for logic programs

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…(The subtlety of reasoning about builtins is not confined to backwards analysis. In fact correctly and precisely encoding the behaviour of the builtins is often the most difficult part of any analysis [33,36]. )…”
Section: Backwards Mode Inferencementioning
confidence: 99%
“…(The subtlety of reasoning about builtins is not confined to backwards analysis. In fact correctly and precisely encoding the behaviour of the builtins is often the most difficult part of any analysis [33,36]. )…”
Section: Backwards Mode Inferencementioning
confidence: 99%
“…EPos loses precision in several programs, but still performs reasonably well. (Goal-independent analysis precision comparisons for EPos and Def are given in (Heaton et al, 2000) and ). These show that EPos loses significant precision, whereas Def gives precision close to that of Pos.…”
Section: Domains: Timings and Precisionmentioning
confidence: 99%
“…Pos is more expressive than Def , but studies have shown that Def analysers can be faster than comparable Pos analysers (Armstrong et al, 1998) and, in practice, the loss of precision for goal-dependent groundness analysis is usually small (Heaton et al, 2000). This paper is a development of (Howe & King, 2000) and is an exploration of the representation of Boolean functions for groundness analysis and the use of Prolog as a medium for implementing all the components of a groundness analyser.…”
Section: Introductionmentioning
confidence: 99%
“…However, Pos-based analyzers do not come with any efficiency guarantee as they require in the worst case exponential number of iterations or exponentially large data structures [11]. More abstract domains [21,23] have been proposed, offering different trade-offs between the precision and the efficiency of analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Con is the least precise abstract domain for groundness analysis. The parametric groundness analysis is thus less precise than a groundness analysis that uses a more precise abstract domain namely Pos [32], Def [21] or EPos [23]. However, a Con-based groundness analysis is much more efficient than groundness analyzers based on more precise abstract domains.…”
Section: Introductionmentioning
confidence: 99%